The Effect of Achievement Assessment, Competence and Position Promotion on Employee Performance with Job Satisfaction as an Intervening Variable in The Office of The Regional Financial and Asset Management Agency (BPKAD) in Toba Regency - Dede Herardi Setiawan; M. Chaerul Rizky (CV. Doki Course and Training, 2026)
This study aims to determine the direct and indirect influence of achievement assessment, competence and position promotion on employee performance with job satisfaction as an intervening variable at the Regional Financial and Asset Management Agency (BPKAD) Office in Toba Regency. The method used is quantitative research that leads to causal research or causal relationships. The population of this study is all ASN employees which is 52 people, while the sample extraction technique is used through non-Probability Sampling using saturated samples, because the population is below 100. The data analysis technique used through SmartPLS 4.0 consists of three stages, including the Outer Model test, the Inner Model and the research Hypothesis test (Bootstrapping). The results of the study show that the assessment of achievement, competence, position promotion and job satisfaction has a positive and significant effect on the performance of employees at the Regional Financial and Asset Management Agency (BPKAD) Office in Toba Regency. And the results of the indirect influence research found that the assessment of achievement, competence and promotion of positions had a positive and significant effect on employee performance through job satisfaction at the Regional Financial and Asset Management Agency (BPKAD) Office in Toba Regency.